Practitioner perceptions: Critical junctures and the global emergence and challenges of fact-checking. (October 2019) - Amazeen, Michelle A
Since 2003 and the emergence of FactCheck.org in the United States, fact-checking has expanded both domestically and internationally. As of February 2018, the Duke Reporter's Lab identified nearly 150 active initiatives around the world. Seen as a professional reform movement in the journalistic community, this research explores fact-checker perceptions of why the practice is spreading globally at this point in time. Using a phenomenological approach, two focus groups were conducted among fact-checkers during the 2015 Global Fact-checking Summit in London, England. Participants shared rich experiences about conditions and contexts surrounding the emergence and challenges facing their organizations including perceived public disempowerment, declines in journalism, technological changes, and socio-political strife. Ultimately, as the purpose of this research is to help future fact-checkers around the world become aware of the circumstances under which fact-checking is most likely to emerge and thrive (or fail), recommendations from current global practitioners are offered.